The mechanobiology of extracellular matrix: a focus on thrombospondins - Ying Zhao; Ting Lei; Xin Ge; Liumeizi Fan; Yinbin He; Zhou Yu; Sheng Hu (Cell Communication and Signaling)
Abstract Mechanosensitive thrombospondins (TSPs), a class of extracellular matrix (ECM) glycoproteins, have garnered increasing attention for their pivotal roles in transducing mechanical cues into biochemical signals during tissue adaptation and disease progression. This review delineates the context-dependent functions of TSP isoforms in cardiovascular homeostasis maintenance, cardiovascular remodeling, musculoskeletal adaptation, and pathologies linked to ECM stiffening, including fibrosis and tumorigenesis. Mechanistically, biomechanical stimuli regulate the expression of TSPs, enabling their interaction with transmembrane receptors and the activation of downstream effectors to orchestrate cellular responses. Under physiological mechanical stimuli, TSP-1 exhibits low-level expression, contributing to the maintenance of cardiovascular homeostasis. Conversely, under pathological mechanical stimuli, upregulated TSP-1 expression activates downstream signaling pathways. This leads to aberrant migration, proliferation, adhesion of cardiovascular cells, and collagen deposition, ultimately resulting in diseases including but not limited to atherosclerosis, pulmonary arterial hypertension (PAH), and myocardial fibrosis. In load-bearing musculoskeletal tissues, TSP-1 facilitates the mechanical adaptation of skeletal muscle and promotes cortical bone formation, whereas TSP-2 regulates chondrogenic differentiation. Within fibrotic and neoplastic tissues characterized by altered matrix stiffness, TSP-1 and − 2 exacerbates tissue fibrosis and tumor progression through transforming growth factor-β (TGF-β)-mediated signaling pathways. These findings establish TSPs as critical mechanochemical switches that govern tissue homeostasis and maladaptation. Clinically, the isoform-specific expression patterns of TSPs correlate with disease severity in atherosclerosis, osteoarthritis, and fibrotic tissues, highlighting their potential as mechanobiological biomarkers. Therapeutically, targeting force-sensitive TSP–receptor interfaces or mimicking their conformational changes under mechanical loading offers innovative strategies for treating mechanopathologies. This review provides a framework for understanding TSP-mediated mechanotransduction across scales, bridging molecular insights for translational applications in mechanopharmacology and ECM-targeted regenerative therapies.